Disability, work, and cash benefits - Mashaw, Jerry L. (W.E. Upjohn Institute for Employment Research, 1996)
Reviews the US Social Security disability programme, with a view to determining whether rehabilitation and work could be incorporated in the income programme without greatly expanding costs or weakening the right to benefit for disabled persons.